The Apotheosis of the Apothecary: Retailing and Consuming the Meaning of a Historic Site - Litt, Paul (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1999)
AbstractThis paper examines how history is interpreted and understood at the Niagara Apothecary, an early 1970s heritage restoration project that is operated as a Victorian-era pharmacy museum in Niagara-on-the-Lake, Ontario. It recounts the history of the restoration of this historic site to show the variety of influences and interests that have shaped the history it presents. The apothecary's setting in Niagara-on-the-Lake, a mecca for heritage tourism and consumerism, makes it an interesting case study of how history is communicated to a popular audience. To this end, the nature of the tourist experience at Niagara-on-the-Lake in general and the apothecary in particular are explored. The paper contrasts the professional historian's emphasis on objectivity and context with the material, romantic, specialised and consumer-friendly strategies that are employed in the presentation of the past at the apothecary.